An Analisys of Language Death in Tanah Sirah, Lubuk Begalung District, Padang - Muthia Damaiyanti; Edwar Kemal (Politeknik Negeri Padang, 2014)
Language is a medium of communication and it is also dynamic. Language also is also influenced by internal and external factors. Internal factors are like the users or the human, while the external factors are like the media, globalization era, etc. These causethe language becomes death. The writer focuses on analyzing the language death in Tanah Sirah, Lubuk Begalung sub-district, Padang.The writer collected the data trough note taking and interview. The theories used are from Mcmahon, Campbell and Muntzell. The result shows that noun is the part of speech included as language death. The part of speech that never occurs as language death is adverb and verb.The dominant of the cause of language death is because the things itself had disappeared from the society.